Comparative outcome analysis of pediatric kidney transplant in posterior urethral valves children with or without pretransplant Mitrofanoff procedure. (2nd August 2020) - Rickard, Mandy; Chua, Michael E.; Zu'bi, Fadi; Dos Santos, Joana; Koyle, Martin A.; Lorenzo, Armando J.; Farhat, Walid A.
Abstract: Background: Urinary diversion using catheterizable channel among posterior urethral valve (PUV) patients may help to alleviate the functional concerns of the bladder on the allograft. Herein, we review our series of PUV patients undergoing renal transplants at a single institution to determine outcomes between those with and without pretransplant Mitrofanoff. Methods: PUV cases in our transplant database from 2000 to 2017 were identified. Data collected included clinical demographics, presentation of PUV, bladder function, implementation of dialysis and donor type. Post‐transplant variables included graft function, and bladder function including incontinence and UTI development. Comparison between with vs without pretransplant Mitrofanoff patient groups was performed using Fisher's exact and t test analysis. Results: Overall, 22 cases were analyzed. The majority (77%) had a prenatal diagnosis of PUV, and 23% had a symptomatic presentation. Pretransplant Mitrofanoffs were performed in 40.9% of cases. The overall age at transplant was 10 ± 5 years. Five percent experienced post‐transplant incontinence and 23% UTIs. No difference between groups was noted in variables including age at transplant, the timing of PUV diagnosis. Mitrofanoff group patients had more symptomatic febrile UTIs than those without Mitrofanoff (67% vs 15%; P = .03); however, there was no difference in post‐transplant UTI development. Furthermore, the Mitrofanoff group seems to have later onset of dialysis or need for transplant (age at the start of dialysis 36 ± 56 vs 156 ± 25 months, P < .001). Conclusion: Our study suggests that patients with early PUV diagnoses who develop symptomatic UTI may benefit from early creation of a Mitrofanoff cathetherizable channel, which is associated with delayed ESRD progression and need for dialysis.